Evaluasi Dimensi Afektif Mahasiswa terhadap Etika Ekologis dalam Kegiatan Pendidikan Jasmani Luar Ruang - Rindawan, Rindawan; Niqsanding Sanrijaya; Satria Mulya Jaya (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
Outdoor physical education plays a vital role not only in enhancing physical fitness and motor skills but also in fostering students’ affective dimensions, particularly in promoting ecological ethics. This study aims to evaluate students’ affective dimension regarding ecological ethics and to analyze the relationship between participation intensity in outdoor activities and the development of ecological attitudes. A quantitative descriptiveevaluative approach was employed with 210 active students from the Physical Education Program at Universitas Pendidikan Mandalika selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire encompassing four affective indicators: ecological awareness, environmental concern, emotional involvement, and moral responsibility. Findings indicate a generally high level of affective dimension (mean = 4.21), with ecological awareness and moral responsibility as the highest indicators. One-way ANOVA revealed a significant difference across outdoor activities, with hiking having the most substantial impact. The study recommends integrating ecopedagogy into the outdoor PE curriculum and developing a systematic affective evaluation model to foster students’ ecological character.